2014
DOI: 10.1097/scs.0b013e3182a2ed26
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Remote Epidural Hematoma Secondary to Decompressive Craniectomy

Abstract: Remote epidural hematoma (REDH) is an uncommon complication of decompressive craniectomy. Remote epidural hematomas of the parietal occiput region have been reported only rarely. We report a unique case of delayed-onset bilateral extensive straddle postsagittal sinus and bilateral lateral sinus parietal occiput REDH after decompressive craniectomy, of which volume was approximately 130 mL, with left deviating midline structures. The patient was immediately taken back to the operating room for evacuation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The mechanism of supratentorial remote epidural hematoma after intracranial tumor resection is still not fully elucidated, though a variety of hypotheses have been formulated. Currently, it is commonly accepted that intracranial pressure is reduced after craniotomy due to the substantial loss of cerebrospinal fluid, thereby increasing the dural venous transmural pressure and inducing blood vessel rupture after disorder of the vascular regulation occurs, resulting in epidural hematoma [ 10 12 ]. After the bleeding of the torn blood vessels occurs, the dura is stripped off the inner skull plate to form a hematoma, while the pressure effect produced by the hematoma increases the transmural venous pressure, aggravating the bleeding and resulting in hematoma expansion [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of supratentorial remote epidural hematoma after intracranial tumor resection is still not fully elucidated, though a variety of hypotheses have been formulated. Currently, it is commonly accepted that intracranial pressure is reduced after craniotomy due to the substantial loss of cerebrospinal fluid, thereby increasing the dural venous transmural pressure and inducing blood vessel rupture after disorder of the vascular regulation occurs, resulting in epidural hematoma [ 10 12 ]. After the bleeding of the torn blood vessels occurs, the dura is stripped off the inner skull plate to form a hematoma, while the pressure effect produced by the hematoma increases the transmural venous pressure, aggravating the bleeding and resulting in hematoma expansion [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Benign and malignant lesions each accounted for half of the included cases; thus, remote epidural hematoma appears to be independent of the resected tumor’s pathological grade. Based on a literature review, numerous similar remote epidural hematomas have been reported after trauma surgery or hydrocephalus surgery, and these hematomas were clearly related to reduce intracranial pressure [ 11 , 12 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These hematomas may be ipsilateral, contralateral, or bilateral, including multiple locations. Various hypotheses regarding the pathophysiology of this remote EDH have been suggested [ 3 15 16 28 ]. These hypotheses include a sudden decrease in ICP; massive drainage of CSF; unequal distribution of ICP, which causes brain shifting; underlying coagulopathies; and excessively powerful pin fixation, which penetrates the inner table of the skull bone.…”
Section: Discussionmentioning
confidence: 99%
“…An EDH can develop regionally; adjacently; or distantly, in a remote area that is removed from the operation site [ 1 ]. There are some reports of remote EDHs that occurred after a ventriculo-peritoneal shunt operation [ 3 4 5 6 7 8 9 10 11 12 13 14 ] or a decompressive craniectomy [ 15 16 ]. Few cases of postoperative remote EDHs after brain tumor surgery have been reported [ 2 17 18 19 20 21 22 23 ], especially in posterior fossa surgery [ 24 25 26 27 ].…”
Section: Introductionmentioning
confidence: 99%